(untitled) (Cardiovascular Journal, 2021)
Background: Postoperative cardiac arrhythmias may present as life threatening complications like- cerebrovascular strokes, thrombo-embolic manifestations, inadequate ventricular filling and compromised hemodynamic stability. Amiodarone is an effective drug for various postoperative arrhythmias. Objective of this study is to evaluate the efficacy of Amiodarone in controlling postoperative arrhythmia in our settings at the department of cardiac surgery. Methods: This retrospective observational study involved random selection of 20 patients, who developed potentially life-threatening arrhythmia following cardiac surgical procedures under cardiopulmonary bypass (CPB) at Chittagong Medical College Hospital (CMCH) between January 2018 and December 2020. Amiodarone was used in controlling postoperative cardiac arrhythmia by loading 1000 mg in first 24 hours, followed by 800 mg orally in daily divided doses. Results: Among 20 patients under study, five had valvular replacement, three had ASD closure, one VSD closure, one patient had excision of LA myxoma and in ten patients had undergone CABG. The Mean ± SD of the age of the patients was 50.2 ± 14.7 years. Eleven patients (55%) were female. Atrial fibrillation with rapid ventricular rate occurred in 15 patients, supraventricular tachycardia in two and ventricular tachycardia three patients. Targets were achieved in all 20 of these patients. Among them 13 (65%) reverted to sinus rhythm, in other 7 AF persisted but ventricular rates became below 100/m with hemodynamic stability. The Mean ± SD of the time required for target achievement was 8.9 ± 7.4 hours. There was no perioperative death in these patients. Conclusion: Amiodarone is an effective medication in combating both atrial and ventricular arrhythmia following cardiac surgery employing cardiopulmonary bypass. Cardiovasc j 2021; 14(1): 20-23